PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU PADA SMA NEGERI KECAMATAN KOTA JUANG KABUPATEN BIREUEN - Zubir; Azhari (LPPM-UNIKI, 2021)
The study was conducted on 116 state high school teachers in Juang City District, Bireuen Regency, with the aim of knowing the effect; 1). The leadership of the principal on the performance of the teachers of the State Senior High School of Juang City, Bireuen District. 2). Work motivation on the performance of teachers in SMA Negeri Juang City District, Bireuen Regency. 3). Job satisfaction with the performance of teachers of SMA Negeri, Kota Juang District, Bireuen Regency, as well as 4). The influence of principal leadership, work motivation and job satisfaction on the performance of teachers in SMA Negeri, Kota Juang District, Bireuen Regency. This type of research is quantitative with descriptive analysis methods and path analysis. The results of the research show, in a descriptive analysis that; a) Principal Leadership Factors including good in supporting teacher performance. The teacher assessment score on the Principal's Leadership reaches 82.59%, b) The level of teacher work motivation, is already good, reaching 82.27% of the ideal conditions in achieving teacher performance, and c) Teacher job satisfaction has shown good things, reaching 82 , 88% of which is expected to improve teacher performance. While the results of the path analysis showed the influence of the principal's leadership on teacher performance was 7.97%. There is an influence of the teacherwork motivation factor on the performance of SMAN teachers in Juang City, Bireuen Regency, which is 9.44 percent. The job satisfaction factor is also a factor that has a very high effect on teacher performance, namely 15.11%. The results of the analysisof the coefficient of determination explain that the contribution of the principal's leadership, work motivation and teacher job satisfaction to the performance of high school teachers in Juang City, Bireuen Regency, is 26.2%.